Pelatihan Pengolahan Tanaman Herbal Berkhasiat untuk Sistem Imun di Desa Lainungan - Hamdayani Lance Abidin; Sulaeman Sulaeman; Nurzadrina Wahyuddin; Anis Rozan Habar; Yolanda Putri Budi (Penerbit Goodwood, 2026)
increases knowledge of health, therefore assisting partners. Partners can also easily make herbal beverages to strengthen the immune system. Methodology/approach: This community involvement enables partners to work together efficiently. Its goal is to increase knowledge of the need of health and enhancement of immunity. Furthermore, partners can quickly develop herbal beverages that boost the immune system. Results/findings: This community involvement enhances knowledge of health and immunity while benefiting partnering collaborators. The creation of herbal beverages that boost the immune system is made simple for partners, allowing them to easily use natural ingredients to produce health-boosting drinks. This initiative not only supports public health but also provides business opportunities for partners, offering products in high demand. Conclusions: The findings of this activity show the increased knowledge of how the immune system works, the right techniques of preparing herbs to avoid negative effects, and the betterment of participants' capacities in producing herbal beverages supporting immune function. Limitations: Limited costs, facilities and innovations to carry out activities as well as limited experienced personnel or experts who master the immune system and the manufacture of herbal drinks Contributions: Housewives, teenager and farmer groups in the use of herbal resources and the cultivation of efficacious herbal plants.